(3OjHGLI JMaI GdCMQGQs - (3HjQ eMeO GdeYQha HQMeJi GdHQShis; (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s ((3eMeO HGbQHf YfGjJ GdCUagGfi s)
(3ChdgG (B:s
(3MGeOkG def LYd MfGf cd YGQa eNRf CSQGQ ceGd hdSGf cd hGUa eWdY CfhGQ LeGdg TYQ CJjfg CfhGQ LeGT s
(3BNQgG (B:s
(3hef Gddg chf Gdchf GdYUeI hGdYhf hUdi Gddg Ydi eMeO hBdg CLeYjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3cJH GdeNWhW HGddZI GdJQcjIs
(3hQO ai cTa GdXfhf L(B1 (3U` (B361 (3Cf JMaI GdCMQGQ gh deDdaI fhQ GdOjf YHO GdQMef Hf CMeO GdLGei (B891 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs